2023
DOI: 10.1111/jen.13180
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different hormones as dietary supplements on biological characteristics of Coccinella septempunctata L.

Ying Cheng,
Yuhang Zhou,
Haiyan Ran
et al.

Abstract: When Coccinella septempunctata L. was fed on an artificial diet, development was prolonged and survival and reproduction were decreased, thus negatively affecting population growth. Juvenile hormone and moulting hormones are important factors in insect reproduction and development. This study aims to screen out the optimal hormones that can solve the problems such as slow population growth of the C. septempunctata during mass rearing, thus improving their effectiveness as a biological control agent. The effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…In our recent study, we found that exogenous JH treatment significantly shortened the pre-oviposition period of diapausing C. nipponensis female adults [53]. A similar result has also been observed in the oriental armyworm Mythimna separata and C. septempunctata [54][55][56]. Here, we knocked down the key gene CnJhamt1, involved in juvenile hormone synthesis in diapause-sensitive C. nipponensis during the diapause-sensitive period, and we found that the pre-oviposition period of C. nipponensis was significantly prolonged (Figure 6A), which indicated that the gene has an influence on the reproductive capacity of diapause-sensitive C. nipponensis.…”
Section: Discussionsupporting
confidence: 71%
“…In our recent study, we found that exogenous JH treatment significantly shortened the pre-oviposition period of diapausing C. nipponensis female adults [53]. A similar result has also been observed in the oriental armyworm Mythimna separata and C. septempunctata [54][55][56]. Here, we knocked down the key gene CnJhamt1, involved in juvenile hormone synthesis in diapause-sensitive C. nipponensis during the diapause-sensitive period, and we found that the pre-oviposition period of C. nipponensis was significantly prolonged (Figure 6A), which indicated that the gene has an influence on the reproductive capacity of diapause-sensitive C. nipponensis.…”
Section: Discussionsupporting
confidence: 71%
“…We speculated that the decline in egg production and hatching rates of C. septempunctata reared on artificial diets may be caused by downregulation of Met expression. When JH is added to artificial diet, it can significantly improve both egg production and hatching rates ( Cheng et al 2023 ); however, the spatio-temporal expression of Met and regulation of reproduction by Met in C. septempunctata are unclear. In the present study, we utilized the transcriptome database of C. septempunctata to clone the full-length cDNA sequence of Met .…”
Section: Introductionmentioning
confidence: 99%
“…Insects 2023, 14, 902 2 of 12 and more recent work has continued with the aim of discovering more effective diets via the utilization of lepidopterans, dipterans, crustaceans, and juvenile hormones [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%